2021
DOI: 10.3390/ijms221910493
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of Lmj_04_BRCT Domain, a Novel Therapeutic Target: Identification of Candidate Drugs for Leishmaniasis

Abstract: Since many of the currently available antileishmanial treatments exhibit toxicity, low effectiveness, and resistance, search and validation of new therapeutic targets allowing the development of innovative drugs have become a worldwide priority. This work presents a structure-based drug discovery strategy to validate the Lmj_04_BRCT domain as a novel therapeutic target in Leishmania spp. The structure of this domain was explored using homology modeling, virtual screening, and molecular dynamics studies. Candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 97 publications
1
12
0
Order By: Relevance
“…We also showed that the treatment of Leishmania-infected macrophages with 19-2.5 and 19-4LF lowered the expression levels of several Leishmania genes implicated in proliferation (Cyclin 1 and Cyclin 6), pathogen virulence (gp63) and treatment resistance (yip1) In line with our results, these genes were similarly downregulated by CPE2, a recently reported leishmanicidal compound [47]. Importantly, our results demonstrated that 19-2.5 and 19-4LF retained their anti-parasitic potential in vivo since they dramatically reduced the parasite burden in the skin lesion as well as in the spleen of infected mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also showed that the treatment of Leishmania-infected macrophages with 19-2.5 and 19-4LF lowered the expression levels of several Leishmania genes implicated in proliferation (Cyclin 1 and Cyclin 6), pathogen virulence (gp63) and treatment resistance (yip1) In line with our results, these genes were similarly downregulated by CPE2, a recently reported leishmanicidal compound [47]. Importantly, our results demonstrated that 19-2.5 and 19-4LF retained their anti-parasitic potential in vivo since they dramatically reduced the parasite burden in the skin lesion as well as in the spleen of infected mice.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibitors of cyclin-dependent kinases (CDKs) have been reported as suitable candidates for the treatment of leishmaniasis [62][63][64][65]. Recently discovered compounds with leishmanicidal activity have demonstrated the ability to inhibit the expression of such cyclins in Leishmania major [47]. On the other hand, terbinafine resistance locus protein (yip 1) codifying gene, has been detected to be overexpressed in drug-resistant Leishmania strains [42,66,67] Since the peptide 19-2.5 showed activity by inhibiting yip1 gene levels, it might be also considered as a potential candidate against resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several data confirmed that BRCT domain from PES1 protein exhibited a functional importance in cancer development. In Leishmania , LmjPES harbors the firstly identified BRCT domain in these parasites, which has demonstrated to be a promising therapeutic target [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other compounds were found to be inactive. This approach was also used by Peña-Guerrero et al, who validated the Lmj_04_BRCT domain as a novel therapeutic target in Leishmania by a structure-based drug discovery strategy, and experimentally validated in vitro a novel inhibitor (CPE2) against L. major, L. amazonensis, and L. infantum (promastigotes and intracellular amastigotes) among seven virtually selected compounds [149].…”
Section: Recent Technological Advances Enabling the Development Of New Research Tools In The Drug Development Processmentioning
confidence: 99%